Is organic food really the best? - Góralczyk, Katarzyna (Studia Ecologiae et Bioethicae, 2018)
Awareness of environmental pollution, and consequently its adverse impact on everyday human life, is increasing. As a result, the search for food of the best quality has become fashionable. It is therefore important that consumers’ knowledge of food production is the best. Conventional food is generally considered to be less valuable or even dangerous due to the presence of various chemicals within it. Meanwhile, organic food is considered healthier and more valuable. However, numerous scientific studies show that there are no significant differences between organic and conventional foods, both in terms of the presence of contaminants and nutritional values.